2017
DOI: 10.1055/s-0043-118909
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Long-Term Outcome of Primary Aldosteronism in a Norwegian Population

Abstract: Primary aldosteronism (PA) is the most common cause of secondary hypertension (HT). We describe here clinical characteristics, diagnostic procedures, and long-term outcomes in a Norwegian population. All suspected PA patients investigated at a tertiary centre from 1998–2012 were retrospectively evaluated. Inclusion criteria were verified PA after confirmatory testing or otherwise considered highly likely PA. Clinical, biochemical, radiological, and adrenal vein sampling (AVS) findings were analysed. Surgically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…In previous studies, surgical outcomes of APA patients were mainly based on the histopathology of HE staining or AVS instead of functional pathology ( 7 , 12 14 , 18 , 19 ). A study from Mayo Clinic observed the outcome of unilateral adrenalectomy in 263 patients with presumptive unilateral disease diagnosed by imaging and AVS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, surgical outcomes of APA patients were mainly based on the histopathology of HE staining or AVS instead of functional pathology ( 7 , 12 14 , 18 , 19 ). A study from Mayo Clinic observed the outcome of unilateral adrenalectomy in 263 patients with presumptive unilateral disease diagnosed by imaging and AVS.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the predictive factors of postoperative clinical cure of patients included female gender, shorter duration of hypertension and lower level of blood pressure. Citton et al also found that female gender, a fewer number of antihypertensive drugs, and a shorter duration of hypertension were the main predictors of hypertension cure ( 18 ). In addition, the present study developed a model, integrating multiple predictors to predict the prognosis of surgery, which is easy to use and is more accurate than single clinical parameter for the prediction of surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This results from the severe underdiagnosis of PA in Iceland. 19 Finally, we did not search for somatic mutations, such as KCNJ5, a suggested predictor of cure after adrenalectomy 29,30 although controversial. 23…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Within the last couple of years, a special focus was given to endocrine tumors, e. g. of the neuroendocrine system including pituitary tumors and pheochromocytoma / paraganglioma. In addition, three issues were published on primary hyperaldosteronism focusing on the genetic cause of the disease as well as diagnostic and therapeutic options [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Dear Readersmentioning
confidence: 99%